Human Capital Investments and Family Size in Italy: IV Estimates Using Twin Births as an Instrument - Michela Ponzo; Vincenzo Scoppa (Institute of Labor Economics (IZA), 2021)
Human capital investments at an early age appear crucial for individual outcomes. Family size might affect these investments influencing parental time and economic resources invested in children's education. This aspect is related to the children quantity-quality trade-off proposed by Becker that has been investigated only for a few countries because of data limitations. We investigate this issue for Italy – even in the absence of Census data relating family of origin to children's educational outcomes – using many waves of the Survey on Household Income and Wealth of the Bank of Italy and focusing on the educational attainments of 19-22 years old. We use twin births as an instrumental variable to identify exogenous variations in family size. In contrast with the results from other developed countries, we find a significant negative effect of family size on children's education. We show that these findings are robust to a number of checks. The effects appear stronger for women, for low income families and when spacing between births is limited, suggesting that both time and financial constraints are mechanisms at work.
Keywords: J13; J24; I21; C36; 330; educational outcomes; family size; quantity-quality children trade-off; twin births; instrumental variables